The first step is the hardest: conceptualization of digital records curatorship in the information science curriculum at the University of Eswatini. Issue 1 (1st December 2022) - Ngoepe, Mpho; Tsabedze, Vusi
Abstract : The conceptualization of digital records curatorship in the archives curriculum in Africa is gaining momentum as scholars engage on the subject. This was accelerated by the development of the workshop on digital curatorship by the International Council on Archives as part of the implementation of the education leg of the African strategy. This paper reports on the journey towards the customization of digital curatorship module in the information science curriculum at the University of Eswatini. The reporting in the paper was mostly informed by the experience from the involvement of the authors in the project. The paper provides a rationale for integrating the workshop in the curriculum of information science at the University of Eswatini. To conceptualize the digital curatorship module in the curriculum, the authors used a conceptual framework scheme by Jacobs which is linked to the theories of Bernstein in terms of vertical and horizontal knowledge. It is concluded that the University of Eswatini still has a long way to go in the development and implementation of a fully-fledged programme in archives and records management. However, the hardest first step taken by the University of Eswatini is acknowledged as a step in the right direction for development of archival curriculum.